2021
DOI: 10.1108/pr-05-2020-0313
|View full text |Cite
|
Sign up to set email alerts
|

Linking performance pressure to employee work engagement: the moderating role of emotional stability

Abstract: PurposeThe purpose of this paper is to investigate the mediating role of threat and challenge appraisals in the relationship between performance pressure and employees' work engagement, as well as the buffering role of emotional stability, as a personal characteristic, in this process.Design/methodology/approachData were collected using a three-wave research design. Hypotheses were examined with a sample of 247 white-collar employees from French organizations.FindingsPerformance pressure is appraised as either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 84 publications
1
38
1
2
Order By: Relevance
“…Procedurally, and in addition to the two-wave data collection that included a time gap of three weeks, we ensured that there was little ambiguity in the survey questions, gave the assurance of the confidentiality and anonymity of responses and communicated the fact that there were no right or wrong answers to the questions (Podsakoff et al , 2012). Statistically, we ran a CFA version of Harman's single-factor test to determine the extent of the CMV in our data (cf., Kundi et al , 2021). The results showed that the one-factor model produced an extremely poor fit to the data ( χ 2 = 2168.22, df = 229; CFI = 0.75; RMSEA = 0.14; SRMR = 0.10) as compared to our hypothesized model, indicating that our data are not contaminated by CMV.…”
Section: Assessment Of Common Methods Variancementioning
confidence: 99%
“…Procedurally, and in addition to the two-wave data collection that included a time gap of three weeks, we ensured that there was little ambiguity in the survey questions, gave the assurance of the confidentiality and anonymity of responses and communicated the fact that there were no right or wrong answers to the questions (Podsakoff et al , 2012). Statistically, we ran a CFA version of Harman's single-factor test to determine the extent of the CMV in our data (cf., Kundi et al , 2021). The results showed that the one-factor model produced an extremely poor fit to the data ( χ 2 = 2168.22, df = 229; CFI = 0.75; RMSEA = 0.14; SRMR = 0.10) as compared to our hypothesized model, indicating that our data are not contaminated by CMV.…”
Section: Assessment Of Common Methods Variancementioning
confidence: 99%
“…The survey was administered in English since it is spoken by a vast majority of French population and is commonly used in organizational contexts (Kundi et al, 2020(Kundi et al, , 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the goal of this study was threefold. First, on the past, researchers have given more attention to task and relationship conflicts and mostly neglected process conflict, considering it similar to the task conflict (Kuriakose et al , 2019). The majority of researchers (Choi and Cho, 2011; Guenter et al , 2016; Jimmieson et al , 2017; Rispens, 2012) investigated the association between task and relationship conflicts while only a few studies (Greer et al , 2008; van den Berg et al , 2014) have focused on the relationship of process conflict with other types of interpersonal conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of researchers (Choi and Cho, 2011; Guenter et al , 2016; Jimmieson et al , 2017; Rispens, 2012) investigated the association between task and relationship conflicts while only a few studies (Greer et al , 2008; van den Berg et al , 2014) have focused on the relationship of process conflict with other types of interpersonal conflicts. Hence, researchers (Kuriakose et al , 2019; Guenter et al , 2016; van den Berg et al , 2014) have called for further investigation of the interplay among task, process and relationship conflicts. Therefore, this study investigated how and when task and process conflicts relate to relationship conflict.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation